Paragonimus mexicanus (=peruvianus) metacercariae infection Hypolobocera chilensiseigenmanni in Condebamba district (Cajamarca, Perú) - Huiza F., Alina (2000)
Hypolobocera chilensis eigenmanni crabs were collected from small streams during the dry season, 1997 (May to December) in the Chaquicocha area belonging to the district of Condebamba (Department of Cajamarca) in the northern region of Peru. One hundred thirty one crabs were collected, transported and examined in the Parasitology Laboratory by dissection, 27 out of 131 (20,6%) were infected by Paragonimus mexicanus (=peruvianus) metacercariae. The intensity of infection was from 1 to 5 in most of the cases (81,5%) with an average of 4,85 per crab. These data are different from past studies in the same area with higher figures, indicating decreasing tendency in the number of infected crabs.